2009
DOI: 10.1097/brs.0b013e3181956053
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Assessment of Lumbar Facet Distance Spacing and Pediatric Spondylolysis

Abstract: A likely explanation for the etiology of lumbar pars defects is insufficient caudal increase in lumbar interfacet spacing. Further prospective studies are necessary to determine if unaffected individuals with a narrowed interfacet spacing are at increased risk of developing spondylolytic defects later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
3
8
0
Order By: Relevance
“…The boundary of bone and soft tissue is demarcated by dotted lines. 47 Collectively, our findings and many others emphasize an undeniable role of anatomic abnormalities in the isthmus or adjacent bony structures together with consequently altered biomechanics in development of spondylolysis. C, Representative images of alkaline phosphatase staining of cultured BMSCs under osteogenic condition.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The boundary of bone and soft tissue is demarcated by dotted lines. 47 Collectively, our findings and many others emphasize an undeniable role of anatomic abnormalities in the isthmus or adjacent bony structures together with consequently altered biomechanics in development of spondylolysis. C, Representative images of alkaline phosphatase staining of cultured BMSCs under osteogenic condition.…”
Section: Discussionsupporting
confidence: 68%
“…30 This finding is consistent with the previous study where a total of 509 fetal specimens were examined and displayed neither isthmic crack nor separate neural arch. 15,[47][48][49][50] One good example is a study where the transverse interfacet distance was measured among 39 patients with spondylolysis and compared to 42 adults without spondylolysis. A, Representative calcein double labeling images of isthmus in the junctional region (boxed area) between the ventral and dorsal part of the vertebra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that patients with spondylolysis have a smaller caudal increase in the lumbar transverse interfacet distance compared with healthy individuals. 45,48 Therefore, in the present study, radiographic findings included the presence of SBO, the LL angle, and the L1:L5 ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Several reports have described the morphology of the facet joint in spondylolysis. Previous studies that used radiographic images reported that in patients with spondylolysis, the distance of the facet joint in the lower lumbar was reduced 9,10) . This shows an increased load on the pars interarticularis.…”
Section: Discussionmentioning
confidence: 99%